Comparative analysis of benchmark financial and investment models of social welfare and assessment of their long-term prospects for transformation under the influence of global challenges - M. L. Dorofeev (Управление)
Social welfare, including its non-systemic forms, has existed for several centuries and represents an important element of the economic system aimed at overcoming poverty, protecting vulnerable groups, and ensuring social justice. Changes in the role of the state in regulating the economy, particularly in the 20th century, has accelerated the development of the social welfare systems and improved the social protection level in various countries around the world. Demographic changes, population growth, and increase in population and life expectancy have created favourable conditions for improving social protection in the past century. However, today the external environment for the functioning of these systems becomes less favourable: population aging, rapid technological progress, changes in labour market structures, and other global challenges contribute to their further transformation. The article provides a comparative analysis of the benchmark financial and investment models of social welfare (hereinafter referred to as FIMSW) of Bismarck, Beveridge, and the Scandinavian model. It systematises and analyses the factors affecting the establishment and transformation of modern FIMSW in the long term. The state is advised to increase the efficiency of public-type FIMSW and encourage the development of private-type FIMSW in sectors where self-sufficiency is possible. To achieve this, it is advisable to implement stimulating financial policies based on tax incentives, programmes for co-financing and increasing financial literacy of the population.